2020
DOI: 10.3389/fonc.2020.00511
|View full text |Cite
|
Sign up to set email alerts
|

Serum STIP1, a Novel Indicator for Microvascular Invasion, Predicts Outcomes and Treatment Response in Hepatocellular Carcinoma

Abstract: Background: Previous studies reported that stress-induced phosphoprotein 1 (STIP1) can be secreted by hepatocellular carcinoma (HCC) cells and is increased in the serum of HCC patients. However, the therapy-monitoring and prognostic value of serum STIP1 in HCC remains unclear. Here, we aimed to systemically explore the prognostic significance of serum STIP1 in HCC. Methods: A total of 340 HCC patients were recruited to this study; 161 underwent curative resection and 179 underwent transcatheter arterial chemoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Given the lack of distinct clinical manifestations, most diagnosed HBV-linked HCC patients are in the advanced stage and have a poor prognosis. Although some serum biomarkers for early diagnosis have been reported in the literature, the results were not very satisfactory [5][6][7]. Therefore, finding new molecular markers for the early diagnosis, treatment, and prognostic evaluation of HBV-related HCC is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of distinct clinical manifestations, most diagnosed HBV-linked HCC patients are in the advanced stage and have a poor prognosis. Although some serum biomarkers for early diagnosis have been reported in the literature, the results were not very satisfactory [5][6][7]. Therefore, finding new molecular markers for the early diagnosis, treatment, and prognostic evaluation of HBV-related HCC is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…However, MVI is usually difficult to assay before surgery because it depends on pathological examination. Therefore, the development of a noninvasive method that can accurately identify MVI preoperatively has become a research hotspot ( Xu et al, 2019 ; Ma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mao et al found that ASPP2 expression in cancer tissue following TACE is an independent risk factor for HCC recurrence as well as overall survival [9]. Ma et al demonstrated serum STIP1 is a promising biomarker for outcome evaluation, therapeutic response assessment, and microvascular invasion prediction in HCC following TACE [10]. Given this, screening reliable and novel biomarkers for predicting HCC response to TACE treatment is an urgent clinical need.…”
Section: Introductionmentioning
confidence: 99%